Simulium (Hearlea) Vargas, Mart nez Palacios, & D az N jera (Diptera: Simuliidae): Taxonomic revision and cladistic analysis - Coscarón, S.; Esquivel, D. R. Miranda; Moulton, J. K.; Coscarónarias, C. L.; Bernal, S. Ibañez (Zootaxa, 2004)
Simulium (Hearlea) Vargas, Mart nez Palacios, & D az N jera 1957 is comprised of 20 known species that are largely confined to the area between M xico and Guatemala. Herein, all currently recognized species within this subgenus are described, illustrated, keyed (except males), and subjected to phylogenetic analysis. Geographic distributions for each species are also updated. Simulium deleoni Vargas, 1945, is synonymized with S. capricorne De Le n, 1944. Simulium paracarolinae new species, from Guatemala, is described from the larva. A cladistic analysis of all Hearlea species and representatives from three outgroups was conducted using 39 morphological characters. Although different character weighting methods yielded different topologies, all trees agreed that Hearlea is monophyletic is comprised of two species groups, based mainly upon characters of the larva and pupa: the Simulium juarezi group S. ayrozai Vargas, S. burchi Dalmat, S. canadense Hearle, S. capricorne De Le n, S. chiriquiense Field, S. contrerense D az N jera & Vulcano, S. dalmati Vargas & D az N jera, S. delatorrei Dalmat, S. estevezi Vargas, S. ethelae Dalmat, S. juarezi Vargas & D az N jera, S. microbranchium Dalmat, and S. nigricorne Dalmat and the S. carolinae group Simulium (Hearlea) carolinae De Le n, S. gorirossiae Vargas & D az N jera, S. johnsoni Vargas & D az N jera, S. larvispinosum De Le n, S. menchacai Vargas & D az N jera, S. paracarolinae n. sp., and S. temascalense D az N jera & Vulcano.